Grandmother Toe - Carfore, Kimberly Ann (The Trumpeter, 2016)
For decades scholars of the humanities have been going back and forth between nature/culture and civilized/wild dichotomies trying to answer questions about nature and the wild. Do we, as a humanity, need to go back to the wild? Does wilderness exist or is it a social construct? Is the concept of wilderness essentialist? Do we need to conserve the wild? After years of vacillation, discourse becomes stuck in the confines of language and logic. Poetry, art, and other forms of creative expression free concepts from their structural limits. This piece of poetry titled "Grandmother Toe" offers a creative exploration of the concepts of wilderness, ancestry, evolution, expressing a possible way forward through an uncertain future.